Kebijakan Anti-Terorisme Indonesia: Dilema Demokrasi dan Represi - Endi Haryono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
Debates on how to effectively handle the problem of terrorism in Indonesia emerged as the actual threats and attacks occured. Indonesia has already established law on handling terrorism, that was issued by President Megawati Soekarnoputri’s reign in 2002 as the respon to the terrorist bombing at Bali. This paper briefly describes the anti-terrorism policy in Indonesia, the criticisms and notes on the policy, and how the discourse surrounding of the president’s option to involve military actively in the handling of terrorism must be viewed in the context of this policy.